2020
DOI: 10.1099/mgen.0.000432
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of cyanobacterial alkane overproduction reveals stress-related genes and inhibitors of lipid droplet formation

Abstract: The cyanobacterium Nostoc punctiforme can form lipid droplets (LDs), internal inclusions containing triacylglycerols, carotenoids and alkanes. LDs are enriched for a 17 carbon-long alkane in N. punctiforme , and it has been shown that the overexpression of the aar and ado genes results in increased LD and alkane production. To identify tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Genome-scale modelling data suggested that the higher CEF pressurises the cells to use less energy-efficient pathway, which in turn leads to the lower quantum efficiency of photosynthesis and result in slower growth (Berla et al, 2015 ). It was also suggested that alkanes are essential for maintaining proper membrane fluidity and flexibility (Arias et al, 2020 ; Lea-Smith et al, 2016 ). Further, data suggest that alkanes are essential for cyanobacteria to tolerate abiotic stresses including cold temperature (20°C) (Berla et al, 2015 ) and salt (Yamamori et al, 2018 ).…”
Section: Alkane Production By Cyanobacteria and Its Physiological Eff...mentioning
confidence: 99%
See 4 more Smart Citations
“…Genome-scale modelling data suggested that the higher CEF pressurises the cells to use less energy-efficient pathway, which in turn leads to the lower quantum efficiency of photosynthesis and result in slower growth (Berla et al, 2015 ). It was also suggested that alkanes are essential for maintaining proper membrane fluidity and flexibility (Arias et al, 2020 ; Lea-Smith et al, 2016 ). Further, data suggest that alkanes are essential for cyanobacteria to tolerate abiotic stresses including cold temperature (20°C) (Berla et al, 2015 ) and salt (Yamamori et al, 2018 ).…”
Section: Alkane Production By Cyanobacteria and Its Physiological Eff...mentioning
confidence: 99%
“…A comparative transcriptomic analysis was performed recently for the cyanobacterium ( N. punctiforme ) harbouring alkane-overproducing plasmid and control plasmid (Arias et al, 2020 ). The analysis suggested that 177 genes were upregulated and 121 genes were downregulated.…”
Section: Alkane Production By Cyanobacteria and Its Physiological Eff...mentioning
confidence: 99%
See 3 more Smart Citations